2015
DOI: 10.1016/j.jfludis.2015.08.001
|View full text |Cite|
|
Sign up to set email alerts
|

Communication attitudes in children who stutter: A meta-analytic review

Abstract: After reading this article, the reader will be able to: (a) summarise empirical findings with regard to the relationship between communication attitudes and childhood stuttering; (b) describe the different instruments used to measure communication attitudes; (c) discuss the relationship between communication attitudes, age and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 86 publications
(156 reference statements)
1
31
2
5
Order By: Relevance
“…Among schoolage CWS, communication attitude becomes more negative with age. Stokke Guttormsen, Kefalianos and Naess [18], in their meta-analytic review of differences in communication attitude in CWS and CWNS, found that the effect size across studies became larger when the mean age in the sample increased, indicating that larger effect sizes are reported in studies with older school-age children, compared to effect sizes reported in the majority of studies examining preschool children. As expected, there was a statistically significant difference between the boys in the experimental compared to the control group (F=71.850, p=.000, Cohen η 2 =.510), and girls in the CWS versus CWNS group (F=37.930, p=.000, Cohen η 2 =.431).…”
Section: Cws (N=49)mentioning
confidence: 99%
“…Among schoolage CWS, communication attitude becomes more negative with age. Stokke Guttormsen, Kefalianos and Naess [18], in their meta-analytic review of differences in communication attitude in CWS and CWNS, found that the effect size across studies became larger when the mean age in the sample increased, indicating that larger effect sizes are reported in studies with older school-age children, compared to effect sizes reported in the majority of studies examining preschool children. As expected, there was a statistically significant difference between the boys in the experimental compared to the control group (F=71.850, p=.000, Cohen η 2 =.510), and girls in the CWS versus CWNS group (F=37.930, p=.000, Cohen η 2 =.431).…”
Section: Cws (N=49)mentioning
confidence: 99%
“…예를 들어 긴 문장을 읽는 경우 일반인의 말속도는 초 당 5.85음절로 말더듬성인의 말속도 5.04음절보다 유의하게 빨랐 다 (Lee, 2010). 반면 성별에 따른 말속도 차이와 관련해서는 남성이 여성보다 빠르다는 결과와 차이가 없다는 결과 등 비일관적인 결과 가 제시되었다 (Ahn, Shin, & Kwon, 2002;Jeon et al, 2011;Lutz & Mallard, 1986;Robb, Maclagan, & Chen, 2004 (Guttormsen, Kefalianos, & Naess, 2015;Silverman & Zimmer, 1979 (Bortfeld et al, 2001;Kools & Berryman, 1971;Tumanova et al, 2014 (Duchin & Mysak, 1987;Leeper & Culatta, 1995;Shin, 2016). 으로 읽기에서 더 빠른 말속도를 보고하였다 (Shin & Han, 2003).…”
unclassified
“…A gaguez pode causar sentimentos de grande dor, angústia e frustração (Guttormsen, Kefalianos, & Naess, 2015;Guitar, 2014;Manning, 2010); a pessoa que gagueja pode vir a ser alvo de pena, correções, gozo, ridicularização, castigo, evitamento, isolamento e desprezo devido à perturbação (Shipley & McAfee, 2015;Guitar, 2014;Manning, 2010). Tal torna-se importante desconstruir na intervenção (Guitar, 2014;Manning, 2010).…”
unclassified
“…Em paralelo, sabe-se que crianças que gaguejam apresentam mais atitudes negativas, comparativamente aos seus pares, na comunicação; tal é considerado por Guttormsen, Kefalianos & Naess (2015), como possível influência no desenvolvimento ou persistência da gaguez.…”
unclassified